2013
DOI: 10.1117/12.2004783
|View full text |Cite
|
Sign up to set email alerts
|

High near-infrared emission intensity of Er3+-doped zirconium oxide films on a Si(100) substrate

Abstract: High crystalline quality erbium-doped zirconium oxide films were deposited on Si(100) by electron beam evaporation in high vacuum. Characteristics of light emission in the telecommunication window from erbium oxide crystal zirconium oxide films were investigated before and after furnace annealing in oxygen atmosphere. The luminescence intensity of the erbium-doped thin film after annealing at 900 °C was 18 times higher than those before thermal annealing. Also, it was observed a decrease in the intensity of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This fact suggests that the probability of the occupancy of Eu 3 þ at the C 2 sites increases upon thermal treatment in oxygen atmosphere, therefore favoring the formation of electric dipoles. In this manner, we confirmed that the electric dipole transitions are hypersensitive to the ligand environment, as already indicated in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This fact suggests that the probability of the occupancy of Eu 3 þ at the C 2 sites increases upon thermal treatment in oxygen atmosphere, therefore favoring the formation of electric dipoles. In this manner, we confirmed that the electric dipole transitions are hypersensitive to the ligand environment, as already indicated in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 72%
“…The increase in emission intensity ( Fig. 3) with increasing film thickness arises due to the increasing volume available for photon-solid interactions [25]. This improvement in the emission intensity increased further following the thermal treatment because the vacancies in the films were filled with oxygen ions [25][26][27].…”
Section: Resultsmentioning
confidence: 93%
“…Other investigations involving thin films, MOFs and coordination polymers have been reported in the literature [18,63,73,78,88,94,133,141,169,178,182,185,201,.…”
Section: Thin Films Metal-organic Framework and Coordination Polymersmentioning
confidence: 99%